2014
DOI: 10.1080/15389588.2013.836597
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Road Crash Injuries in Cambodia: An Evaluation of the Cambodia Road Crash and Victim Information System (RCVIS)

Abstract: Objective Worldwide, 1.24 million deaths and 20–50 million road crash injuries occur annually, with a disproportionate burden on low- and middle-income countries. Facing continued growth in motorized vehicles, Cambodia has begun to address road safety, including the creation of a nationwide road crash surveillance system, the Road Crash and Victim Information System (RCVIS). This study evaluates the RCVIS to understand whether road crash injuries are being monitored efficiently and effectively and to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…It was concluded that factors affecting the occurrence of accidents were not necessarily predictors of outcome severity. 41 , 42 Similarly, the causes of accidents were described in some of the reviewed articles by different methods, such as the opinion of the drivers, the reflected opinion of potential drivers, and evidence of the victims. 16 , 26 , 32 , 33 , 38 As a result of the enactment of the seat belt law, in accordance with suggestions from these studies, a significant drop in certain types of injuries was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that factors affecting the occurrence of accidents were not necessarily predictors of outcome severity. 41 , 42 Similarly, the causes of accidents were described in some of the reviewed articles by different methods, such as the opinion of the drivers, the reflected opinion of potential drivers, and evidence of the victims. 16 , 26 , 32 , 33 , 38 As a result of the enactment of the seat belt law, in accordance with suggestions from these studies, a significant drop in certain types of injuries was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Motorization can indicate increased exposure, and if not accompanied by road safety legislation and adequate enforcement, may also indicate increased risk. Increased motorization was associated with increased rates of traffic fatalities in Germany following reunification in 1989 to 1991 and during times of economic progress in Nepal between 1981 and 2003 and Cambodia between 2006 and 2010 [ 8 , 11 , 12 ]. Estimates from the region with both annual numbers of road traffic fatalities and vehicles registered are unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…First, although RCVIS contains both fatal and non-fatal injuries, we report only on fatalities due to inconsistent reporting among hospitals over the study period which compromised the quality of non-fatal injury data. There is more confidence in the data quality for fatalities, because fatalities are based primarily on police data, which have been shown to be more reliable than hospital data (Parker et al, in press). Nonetheless, reporting on motorcyclist fatalities underestimates the true burden of motorcycle crashes in Cambodia.…”
Section: Discussionmentioning
confidence: 99%